2022
DOI: 10.1029/2021pa004404
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for Identifying and Quantifying Ice Rafted Debris on the Antarctic Margin

Abstract: Quantification of ice rafted debris (IRD) abundances in deep‐sea records is often used as a key proxy for identifying links between ice sheet instability and the oceanic overturning circulation. There currently exist multiple methods to determine IRD content in deep‐sea sediment cores. The preference for a given method is often determined by the accessibility to core material and destructive nature of some methods. While many studies have discussed the caveats between linking IRD to ice sheet dynamics, the unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 88 publications
(176 reference statements)
0
15
0
Order By: Relevance
“…The rigorous comparison of methods commonly used to identify and quantify IRD provided by McKay et al. (2022) is especially timely since IRD is recognized as the fundamental proxy of ice sheet change preserved in deep sea sedimentary records. Recovery of high latitude paleoceanographic records from both hemispheres, especially those with glacial‐interglacial cycles representing warmer periods, has relied extensively on the technological and logistical expertise of IODP (i.e., Sánchez Montes et al., 2022).…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…The rigorous comparison of methods commonly used to identify and quantify IRD provided by McKay et al. (2022) is especially timely since IRD is recognized as the fundamental proxy of ice sheet change preserved in deep sea sedimentary records. Recovery of high latitude paleoceanographic records from both hemispheres, especially those with glacial‐interglacial cycles representing warmer periods, has relied extensively on the technological and logistical expertise of IODP (i.e., Sánchez Montes et al., 2022).…”
Section: Commentarymentioning
confidence: 99%
“…McKay et al. (2022) acknowledge that although larger sample sizes are preferred the method chosen for quantification of IRD within a particular study may be dictated by sampling pressure resulting from a need to analyze several proxies (e.g., Müller et al., 2018) and limited available sediment.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the method employed and decisions made about how to define a Heinrich Layer, there may be significant experimental error in the reported thickness of layers. Indeed, an intercomparison of methods for measuring IRD abundance in cores from the Antarctic margin found that, though methods tend to represent the same trends of IRD, different methods could report IRD counts varying by a factor of two at a given depth in the core (McKay et al 2022).…”
Section: Introductionmentioning
confidence: 99%